Hydrogen Production via Thermal Cracking of Ammonia Using Steel Fiber Catalyst - Bo Zhang; Mingyue Zhao; Kangwei He; Jianye Huang (BioResources)
Due to challenges associated with hydrogen storage and transportation, on-site hydrogen production has garnered significant attention. However, achieving a balance between efficiency and cost remains a critical challenge in the catalytic conversion of ammonia to hydrogen. Catalysts utilizing carbon fiber supports derived from cellulose, which contain a high carbon content, have demonstrated promising dehydrogenation activity in ammonia pyrolysis. One such catalyst component is steel fiber which contains a high content of transition metals and serves as a connection between the carbon element and the metals, which would enhance its catalytic properties. In this study, the catalytic performance of commercial steel fiber for hydrogen production via ammonia pyrolysis was investigated. Activity tests and analytical characterizations revealed that the steel fiber catalyst exhibited excellent catalytic activity, stability, and cyclic performance, enabling COX-free hydrogen production. Characterization results indicated that the catalyst contained over 80 wt% iron atoms and exhibited low surface area. The Fe atoms were further converted into stable Fe-N bonds, with the number of Fe-N bonds decreasing as the reaction temperature increased, thereby accelerating the desorption rate of nitrogen atoms on the catalyst surface and enhancing conversion efficiency.